A morphological assessment of the health status of a cadaver population at the Faculty of Health Sciences, Stellenbosch University, with special reference to tuberculosis (TB) Lesion distribution - Geldenhuys, Elsje-Marie (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.